2020
DOI: 10.1108/qmr-03-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Facades of morality: the role of moral disengagement in green buying behaviour

Abstract: Purpose This study aims to presents the article regarding the influential role of moral inefficacy and moral disengagement to address green intention and behaviour gap among consumers, and how they attain self-exoneration because of the moral dilemma if any exist. Design/methodology/approach The present study is based on semi-structured interviews, using constructivist grounded theory, which offers a platform to investigate, explore and discover psychosocial mechanism that operates among the consumers regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 77 publications
(93 reference statements)
2
13
0
Order By: Relevance
“…Green purchasing intention refers to the motivators that influence consumers' perceptions and provide potential encouragement to behave in a selected manner (Costa et al ., 2021; Ajzen, 1991). Based on empirical studies, the personality of consumers can be said to have an impact on their green purchasing decisions (Duong, 2021), even though difficult situations would cause them to avoid such practices, unless it is considered a moral obligation (Sharma and Lal, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green purchasing intention refers to the motivators that influence consumers' perceptions and provide potential encouragement to behave in a selected manner (Costa et al ., 2021; Ajzen, 1991). Based on empirical studies, the personality of consumers can be said to have an impact on their green purchasing decisions (Duong, 2021), even though difficult situations would cause them to avoid such practices, unless it is considered a moral obligation (Sharma and Lal, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such scenarios created problems for the companies in segmenting and strategizing the green product development for the consumers. It was hard to recognize the purchase intention of green products and their characters with other issues, like product branding, pricing and measuring the products' greenness (Annandale, Morrison-Saunders, & Bouma, 2004;Sharma & Lal, 2020;Sharma, Saha, & Rameshwar, 2019). Moreover, different factors like product selection, self-perception and identity influence the green purchase intention (GPI) of the consumer.…”
Section: Introductionmentioning
confidence: 99%
“…The environmentally-conscious consumers are the people who only want to consume products that have less or no impact on the environment at all [18]. Reference [19] defined green buying behavior as the consumption of a product that has a benefit for the environment, can be recycled, persevered, or responsive towards ecological issues. Previous research found that there was a gap between the desire to buy green products and actual buying behavior, especially among millennials who had environmental concerns but did not apply it to their consumption behavior [2].…”
Section: Environmentally Conscious Consumer Behaviormentioning
confidence: 99%